Pengaruh Penggunaan Metode Proyek Pada Mata Pelajaran IPS di SDN Ngujung 2 Kabupaten Magetan Terhadap Prestasi Belajar Siswa Kelas IV - Marsini Marsini (Indonesian Journal of Social Science Education (IJSSE), 2023)
This study aims to determine the effect of using the project method on social studies subjects at SDN Ngujung 2 Magetan Regency on student achievement in class IV. To examine these problems in more depth, this study used a quantitative approach with a quasi-experimental research method. The location of this research is SDN Ngujung 2, Maospati District, Magetan Regency. Therefore, to accelerate understanding and avoid misunderstanding, appropriate learning approaches and methods are needed, according to the level of psychological maturity of students. The recommended approach in KTSP and K13 is a contextual approach including the learning method. Based on the results of research starting from observations and tests, it can be concluded that the application of the project method greatly influences student achievement. This is evidenced by the results of tests carried out three (3) times during the study showing grade IV students at SDN Ngujung 2 Maospati obtained scores above the average, namely 80-100.